Cortico-Cortical Evoked Potentials in Children With Tuberous Sclerosis Complex Using Stereo-Electroencephalography - Yu, Xiaoman; Ding, Ping; Yuan, Liu; Zhang, Juncheng; Liang, Shuangshuang; Zhang, Shaohui; Liu, Na; Liang, Shuli (Frontiers in Neurology, 2019)
Objectives: Tuberous sclerosis complex (TSC) presents multiple cortical tubers in brain, and it is still difficulty to localize the epileptogenic tuber. The value of cortico-cortical evoked potentials (CCEP) was assessed in epileptogenic tuber localization for tuberous sclerosis complex (TSC) patients using stereo-electroencephalograph (SEEG). Methods: TSC patients, who underwent SEEG and CCEP examination in preoperative evaluation during 2014-2017, and presented postoperative seizure freedom at last follow-up, were enrolled (n=11). CCEPs were conducted by stimulating every two adjacent contacts of SEEG electrodes and recording on others contacts of SEEG electrodes in one epileptogenic tuber ant its early-stage propagating tuber, and their perituberal cortexes in each patient. The CCEP was defined as positive when N1 and/or N2 wave presented, and then the occurrence rates of positive CCEPs were then compared among different tubers and perituberal regions. Results: Occurrence rates of positive CCEP from epileptogenic to early propagating tubers and epileptogenic tuber to perituberal cortex were 100%, significantly higher than the occurrence rates of CCEP in other locations. The occurrence rate of CCEP from peripheral portions of epileptogenic tubers to peripheral portions of early propagating tubers or perituberal cortex was 100%, and significant higher percentage than the rate of CCEP from peripheral regions of early propagating tubers to peripheral portions of epileptogenic tubers , from central of early propagating tuber to central portions epileptogenic tubers, from perituberal cortex to center part of epileptogenic tuber, and between perituberal cortex. Conclusion: Epileptogenic tubers presented much more diffusive connectivity with other tubers and cortex than any other connectivity relationship across tuber species, and peripheral region of epileptogenic tubers presented greatest connectivity with tubers and cortex. CCEP can be an effective tool in epileptogenic tubers localization.